2012
DOI: 10.1155/2012/657026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymol and Carvacrol, Constituents ofThymus vulgarisL. Essential Oil, on the Inflammatory Response

Abstract: Thyme (Thymus vulgaris L., Lamiaceae) is an aromatic and medicinal plant that has been used in folk medicine, phytopharmaceutical preparations, food preservatives, and as an aromatic ingredient. The effect of Thymus vulgaris essential oil (TEO) and its isolated constituents thymol and cavacrol (CVL) were studied in the following experimental models: ear edema, carrageenan-induced pleurisy, and chemotaxis in vitro. In the pleurisy model, TEO, CVL, and thymol significantly inhibited inflammatory edema. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
184
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(199 citation statements)
references
References 39 publications
13
184
0
2
Order By: Relevance
“…The irritating symptoms were more pronounced in Ala EO than in the rest of EOs. This may be due to the irritating effect of thymol in this EO (Fachini-Queiroz et al, 2012). It contained over 65% thymol which is much higher than that of Ofl (49.6%), Tar (48.8%), Bal (53.6%) Buta (15.8%) and Yil (6.5%).…”
Section: Observations Of Mice Dosed With Eos At 2000 µL/kg Body Weightmentioning
confidence: 87%
“…The irritating symptoms were more pronounced in Ala EO than in the rest of EOs. This may be due to the irritating effect of thymol in this EO (Fachini-Queiroz et al, 2012). It contained over 65% thymol which is much higher than that of Ofl (49.6%), Tar (48.8%), Bal (53.6%) Buta (15.8%) and Yil (6.5%).…”
Section: Observations Of Mice Dosed With Eos At 2000 µL/kg Body Weightmentioning
confidence: 87%
“…10 µl of thyme n-hexane extract was injected in Trace GC Ultra-ISQ mass spectrometer with a direct capillary column TG-5MS (30 m×0.25 mm×0.25 µm). Column temperature, 60°C (1 min) to 180°C at 3°C/min; injector temperature, 220°C; detector temperature, 220°C; split ratio, 1:10; carrier gas, helium; flow rate, 1.0 ml/min (Fachini-Queiroz et al, 2012). The mass spectra of the identified components were determined by comparison to the Wiley Registry of mass spectral database 8 th edition.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%
“…It has been reported that Thymus vulgaris essential oil and carvacrol inhibit leukocyte migration in carrageenan-induced pleurisy. In ear edema, carvacrol reduced edema formation, exerting a topical antiinflammatory effect; however, thymol did not reduce edema formation but presented an irritative response, probably dependent on histamine and prostanoid release (30). It has been shown that galectin-3, expressed by all immune and inflammatory cell types (31), has a role in allergic inflammation (32).…”
Section: Discussionmentioning
confidence: 99%